Identification and control of the motor-drive servo turntable with the switched friction model - Zhang, Qian; Wang, Qunjing; Ninghao, Cui (IET electric power applications, 2020)
In this study, the identification and control scheme of the motor-drive servo turntable are researched to achieve accurate tracking. Firstly, the input–output identification experiments are designed and realised for the global model of motor-drive servo turntable. The order of the global controlled auto-regressive model is determined by the Akaike information criterion, and the parameters are estimated by a particle swarm optimisation-cuckoo search algorithm. Secondly, the switched friction model is built combining the LuGre structure and the Stribeck curve. The switching conditions and the parameters of the switched friction model are determined though the input–output and the friction experiments. A constrained multi-objective optimisation problem is constructed for the parameter identification of the switched friction model. It is solved via a fuzzy comprehensive evaluation. Finally, the composite control strategy, in which the proportional–integral–derivative controller and model-based friction observer are combined, is proposed in the azimuth angle system of the motor-drive servo turntable. The trajectory tracking results in simulation and experiment illustrate the effectiveness of the proposed switched model, identification method, and composite control strategy.